The Relationship of Smoking Hazard Message to Smoking Behavior in Students of North Sumatra State Islamic University - Riski Agussalim Siregar; Putra Apriadi Siregar (Universitas Islam Negeri Sumatera Utara, Medan, 2022)
Cigarettes are still a problem in the world and in Indonesia. The policy of pictorial message on cigarette packaging is regulated in Permenkes No. 28 of 2013 concerning the inclusion of warnings and health information on tobacco product packaging. The purpose of this study is to determine the Effect of Cigarette Danger Messages on Cigarette Packs on Smoking Behavior of North Sumatra State Islamic University Students. This research is quantitative research with a cross-sectional research design. This research was conducted at the State Islamic University of North Sumatra. The research period began in January-August 2021. The population in this study was all male students of North Sumatra State Islamic University which amounted to 13,598 students. The sample in this study was as many as 400 respondents in male students of North Sumatra State Islamic University. The data analysis of this study is univariate analysis with descriptive and bivariate analysis with correlation test. The results showed that there was an association between smoking message images causing oral cancer (p-value <0.001 r = -0.596), smoking message images causing lung cancer (p-value <0.001 r = -0.620), smoking message images causing throat cancer 1 (p-value <0.001 r = -0.536), smoking images causing lung and larynx cancer (p-value <0.001 r = -0.537) and smoking images causing laryngeal cancer (p-value <0.001 r = -0.621) smoking behavior students of UIN North Sumatra. It is hoped that the Health Office and the Ministry of Health will review or update the images on cigarette packs with more effective ones to be enlarged in order to reduce the number of smokers in Indonesia. Keywords: Cigarette hazard message; Smoking behavior; Student